2022
DOI: 10.21037/qims-21-981
|View full text |Cite
|
Sign up to set email alerts
|

Associations between carotid atherosclerotic plaque characteristics determined by magnetic resonance imaging and improvement of cognition in patients undergoing carotid endarterectomy

Abstract: Background: To determine the predictive value of carotid plaque characteristics for the improvement of cognition in patients with moderate-to-severe carotid stenosis after carotid endarterectomy (CEA), using vessel wall magnetic resonance imaging (MRI).Methods: This was a prospective cohort study. Patients with unilateral, moderate-to-severe carotid stenosis referred to the Peking University Third Hospital for CEA were prospectively recruited and underwent carotid vessel wall MRI within 1 week before CEA. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…• Broader applications: extending the use of our enhanced FCM algorithm beyond MRI image segmentation to other domains, such as natural language processing or environmental monitoring, carotid atherosclerotic plaque etc. [52,53] could prove beneficial. This would test the algorithm's versatility and adaptability to various data types.…”
Section: Future Workmentioning
confidence: 99%
“…• Broader applications: extending the use of our enhanced FCM algorithm beyond MRI image segmentation to other domains, such as natural language processing or environmental monitoring, carotid atherosclerotic plaque etc. [52,53] could prove beneficial. This would test the algorithm's versatility and adaptability to various data types.…”
Section: Future Workmentioning
confidence: 99%
“…As we all know, MRD detection often requires a high sequencing depth, the sensitivity of ctDNA analysis is limited, and when VAF lowers close to LOD, the number of specific variants in the sample may be demanding. In addition, the tumor fraction of cfDNA varies between cancer entities and even between patients with the same cancer entity ( Bachet et al, 2018 ; Normanno et al, 2018 ; Jiang and Yan, 2021 ; Huo et al, 2022 ). In some ctDNA-based studies, it has been found that tumor micrometastases represent a higher tumor burden than residual local disease, and therefore can shed higher ctDNA levels ( Azad et al, 2020 ; Tie et al, 2021 ).…”
Section: Challenges Of Mrd Detectionmentioning
confidence: 99%
“…Moreover, research exploring the associations between carotid atherosclerotic plaque characteristics and cognitive improvement postsurgery sheds light on the intricate interplay between vascular health and neurological function. [15] To further establish the soundness of our study, we will also integrate findings from studies such as the investigation into anatomical characteristics affecting surgical approaches in lumbar fusion procedures and the image-based visualization of stents in mechanical thrombectomy for acute ischemic stroke cases. [16,17] Overall, compared with artificial neural networks with a single hidden layer, deep learning has stronger expressive and feature-learning abilities.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Moreover, research exploring the associations between carotid atherosclerotic plaque characteristics and cognitive improvement postsurgery sheds light on the intricate interplay between vascular health and neurological function. [ 15 ] Through the application of machine learning approaches, a novel study aims to identify risk factors associated with postoperative infection following mitral valve surgery, a critical area in cardiac surgery. [ 12 ] Relative to a shallow neural network, deep learning uses a deep neural network with multiple hidden layers, which can better simulate the structure of the human cerebral cortex, process the data input to the neural network in layers, and use each layer of the network to extract different levels of, which helps the machine obtain more hidden information.…”
Section: Introductionmentioning
confidence: 99%